Linguistics and Extra Linguistics Used in Grammar for Teaching English - Alicia, Dona (International Journal Labs, 2022)
Background: Language has an important position in life because it can change anything just by saying something. A Human being needs language to do interaction. At least every creature in the world has its language. Besides, for a human language is different. Aim: This article concerns a description of things that are felt by the subject of the research relates to Grammar and something such as students' interest to speak the English language. Method: The method in this research is descriptive qualitative with data sources in the document of record. The data collection method used the observation and note method. The researcher used the interview technique of data collection and the researcher used thematic analysis in data analysis. Findings: It is revealed that students used regular and irregular verbs when speaking in class. The interpretation of student's ability on using regular and irregular verbs in speaking is low because the students are not able to use them.